The impact and mechanism of polycentric structure within Chinese cities on carbon emission intensity - ZOU Xuan, YANG Xu, LIU Chen (Ziyuan Kexue, 2024)
[Objective] As China transitions from mid-stage to late-stage urbanization, the polycentric structure of cities is accelerating. This study explored its impact on carbon emission intensity and the underlying mechanisms. From a spatial planning perspective, it aimed to provide new insights for low-carbon city construction. [Methods] The study examined 279 prefecture-level and above cities in China from 2006 to 2020. Using a two-way fixed effects model, instrumental variables, and propensity score matching, it empirically tested the carbon emission reduction effects of the urban polycentric structure and its underlying mechanisms. [Results] (1) From 2006 to 2020, urban carbon emission intensity showed a declining trend. Spatially, it exhibited a core-periphery structure and provincial boundary phenomena, with minor changes in the east-west gap and an increase in the north-south gap. The urban polycentric structure showed an upward trend with stable geographic clustering characteristics. (2) The polycentric structure significantly reduced carbon emission intensity, but there is regional heterogeneity. It was higher in eastern and western cities compared to central cities and higher in southern cities compared to northern cities. Additionally, it was only present in economically advanced cities and cities with a large population. (3) The mechanism analyses indicated that the urban polycentric structure reduced carbon emission intensity through three pathways: promoting faster development of the service industry, optimizing land use structure, and attracting high-productivity enterprises. However, whether enterprise location choices result in sectoral-specific or mixed clustering varied between cities. [Conclusion] In the new stage of urbanization, supporting the development of polycentric cities is necessary. However, it is crucial to understand the preconditions for the effective carbon emission reduction effects of the urban polycentric structure and to create smooth transmission channels.